A CONCEPTUAL PAPER ON PRESTIGE AND ACCREDITATION AS THE KEY DETERMINANTS INFLUENCING STUDENTS’ INTENTION TO PURSUE AN ACCOUNTING COURSE - Lucy Batchy Gabriel Puem; Saifulrizan Norizan; Chan Ai Nyet; Lulu Jonathan; Tina Stephen Enggong (International Journal of Accounting, Finance and Business, 2022)
This is a conceptual paper of a future study based on the review of literature relatedto accounting education by the previous researchers. In response to global competitiveness inhigher education, prestige and accreditation have become crucial aspects in the selection ofthe right programmes among university students in Malaysia. Students have to take intoaccount many things when choosing a programme major and a career. The main objective ofthis study was to identify the determinants or factors affecting the intention to pursue anaccounting programme. This conceptual paper went on to analyse the issues, concepts, andobjectives for the forthcoming study through several literatures of various disciplines. Theconceptual paper signifies supplemental literature for academics as a reference for theirresearch. The result of this future research may provide information to the government informulating policies that enable students to pursue accounting programmes that produce thehighest number of chartered accountants in Malaysia. It is hoped that the initiatives willproduce many accountants and thus expedite the countries’ aspirations of becoming fullydeveloped nations in due time.